Using registries to recruit subjects for clinical trials - Tan, Meng H.; Thomas, Matthew; MacEachern, Mark P. (Contemporary clinical trials, 2015)
We studied the use of patient/disease registries to recruit potential subjects for prospective clinical trials — describing the number, types and major benefits of using this approach. In December 2013, we conducted a focused database search in PubMed, EMBASE, and Web of Science for studies (English language only) that used registries to recruit subjects for clinical trials published in 2004–2013. Of the 233 unique citations identified, 21 used registries to recruit subjects — 10 papers and 11 abstracts. Pearling and search for subsequent full papers of the abstracts identified 4 more papers. Our analysis, based on these 25 citations, showed that 14 are related to cancer, 3 to diabetes mellitus, 1 each to stroke, asthma, and celiac disease and 5 are disease neutral. Many types of registries (population-based cancer, quality improvement, disease-specific, web-based disease-neutral registries, local general practice registers, and national health database) are used to recruit subjects for clinical trials and uncover new knowledge. Overall, 16 registries are in the US, 4 in UK, 1 each in Canada, Spain, and Australia and 1 involved in many countries. Registries can identify very large number of subjects for screening for eligibility for clinical trials, especially in very large trials, rare disease trials, and trials involving minority patients. Registries can retrospectively identify very large numbers of potential subjects for screening for eligibility and enrollment in prospective clinical trials. This matching can lead to more timely recruitment and help solve a major problem in conducting clinical trials.